2004
DOI: 10.1055/s-2004-836121
|View full text |Cite
|
Sign up to set email alerts
|

Combined Reconstruction of the Diabetic Foot Including Revascularization and Free-Tissue Transfer

Abstract: Diabetic patients, presenting with both peripheral vascular disease and large soft-tissue defects, are too often treated by primary amputation. A combined revascularization and free-tissue transfer procedure can extend limb salvage in these patients. The authors report their experience over 4 years with 19 diabetic patients with peripheral vascular disease and large soft-tissue defects of the foot requiring free-tissue transfer. Although there was a 100 percent flap survival, early local wound problems occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 28 publications
1
24
0
1
Order By: Relevance
“…12 Puskas et al reported a 34% incidence of surgical wounds of the lower limbs submitted to saphenous vein stripping for myocardial revascularization. 13 Subintimal angioplasty without stenting has been widely approached in the literature, [1][2][3][4][5][6][7][8][9][10][11] and is corroborated by our case report.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…12 Puskas et al reported a 34% incidence of surgical wounds of the lower limbs submitted to saphenous vein stripping for myocardial revascularization. 13 Subintimal angioplasty without stenting has been widely approached in the literature, [1][2][3][4][5][6][7][8][9][10][11] and is corroborated by our case report.…”
Section: Discussionsupporting
confidence: 72%
“…Limb revascularization associated with use of grafts and surgical flaps can increase salvation rates in these patients. 1 Use of subintimal angioplasty for the treatment of occlusive atherosclerotic lesions of the lower limbs was described for the first time by Bolia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that salvage, provides a better quality of life for patients with diabetes than amputation, and increases their 5‐year survival rate (Chou et al, ; Oh, Lee, & Hong, ; Randon et al, ; Verhelle, Lemaire, Nelissen, Vandamme, & Heymans, ). The mortality rate of patients with diabetes following amputation is high, between 39% and 80% at 5 years (Chou et al, ; Hong & Oh, ; Oh et al, ; Moran, Illig, Green, & Serletti, ; Moulik, Mtonga, & Gill, ) and amputation of the contralateral limb occurs within 2 years of the first amputation in approximately 50% of patients (Ecker & Jacobs, ; Kucan & Robson, ; Oh et al, )…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that salvage, provides a better quality of life for patients with diabetes than amputation, and increases their 5-year survival rate (Chou et al, 2016;Oh, Lee, & Hong, 2013;Randon et al, 2010;Verhelle, Lemaire, Nelissen, Vandamme, & Heymans, 2004). The mortality rate of patients with diabetes following amputation is high, between 39% and 80% at 5 years (Chou et al, 2016;Hong & Oh, 2012;Oh et al, 2013;Moran, Illig, Green, & Serletti, 2002;Moulik, Mtonga, & Gill, 2003) and amputation of the contralateral limb occurs within 2 years of the first amputation in approximately 50% of patients (Ecker & Jacobs, 1970;Kucan & Robson, 1986;Oh et al, 2013) The combination of revascularization with free tissue transfer for the treatment of diabetic lower leg and foot soft tissue defects leads to successful salvage of the diabetic limb (Briggs, Banis Jr., Kaebnick, Silverberg & Acland, 1985;Chou et al, 2016;Hong & Oh, 2012;Moran et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Pedicled skin flaps, in contrast, had the highest rate of partial loss as well as higher rates of complete loss and amputation compared with free skin flaps. As compared with free skin flaps, pedicled muscle flaps had higher partial flap loss rate and 6 (4.7) 0 (0) 1 (16.7) Serratus anterior 28 4 (3.1) 0 (0) 0 (0) Tensor fascia latae 30 2 (1.6) 0 (0) 0 (0) Vastus lateralis 27 …”
Section: Discussionmentioning
confidence: 97%